Supported FeNi bimetallic catalyst and its preparation method and application
Through the use of supported FeNi bimetallic catalysts, the problems of high cost and poor stability of existing precious metal catalysts in fatty acid non-hydrogenated deoxygenation reactions are solved, and efficient and economical biofuel preparation is achieved.
Patent Information
- Application Number
- CN202310353949.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-04-04
AI Technical Summary
Existing precious metal catalysts have high cost and poor stability in the non-hydrogen deoxygenation reaction of fatty acids, making it difficult to achieve efficient and economical biofuel preparation.
The supported FeNi bimetallic catalyst is used to improve catalytic activity through the synergistic action, geometric modification and electronic modification of bimetallic. The catalyst is composed of a highly dispersed alloy compound composed of Fe and Ni doping each other. The iron content is 5 to 15%, the nickel content is 5 to 21%, the support is selected from activated carbon, Al2O3, etc., and the particle size is 50 to 200 nm.
It has achieved efficient catalytic fatty acid deoxygenation under non-hyperhydrogen conditions, significantly improved product conversion and deoxygenation, and good catalyst stability and reusability, reducing production costs.
Smart Images

Figure CN116139865B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of non-hydrogenation of fatty acids, and in particular to a supported FeNi bimetallic catalyst and a preparation method and application thereof. Background Art
[0002] With the rapid development of the global economy, the consumption rate of non-renewable fossil energy has increased rapidly. At present, all countries in the world are vigorously developing biomass energy. Biomass energy is cheap and easy to obtain, has huge reserves, and can be recycled and renewed, which is conducive to achieving the goal of carbon neutrality [7]. Oils and fats are an important choice for biomass utilization. They are widely distributed in nature. For example, there are abundant woody oils in the seeds of various plants and the tissues and organs of animals.
[0003] In order to facilitate the study of reaction characteristics, fatty acids are often used as model compounds of oils and fats. According to the degree of saturation, they can be divided into saturated fatty acids and unsaturated fatty acids. Common fatty acids in oils and fats include lauric acid (C 12:0 ), myristic acid (C 14:0 ), palmitic acid (C 16:0 ), stearic acid (C 18:0 ) and palmitic acid (C 16:1 ), oleic acid (C 18:1 ), linoleic acid (C 18:2 ), linolenic acid (C 18:3 ) and other unsaturated acids. Fatty acids can effectively reduce the acid value and improve combustion characteristics after deoxygenation treatment. The corresponding main deoxygenation products are long-chain alkanes and long-chain olefins. Among them, long-chain alkanes are easier to generate thermodynamically and are the main components of high-quality biodiesel, kerosene and aviation kerosene. In order to achieve the goal of carbon neutrality, the catalytic deoxygenation of oils and fats to prepare biofuels has important research significance and development prospects.
[0004] At present, a large number of fatty acid deoxygenation catalyst preparation research focuses on the development of noble metal-based (such as Pd, Pt, Ru, etc.) catalysts. However, the preparation cost of noble metal catalysts is high, and the metal particles are easily leached by acidic fatty acids at high temperatures, resulting in poor catalyst reusability and stability. Therefore, it is very important to develop a transition metal catalyst with good activity and stability. Zhang et al. (Zhang Z, Chen Z, Gou X, Chen H, Chen K, Lu X, Ouyang P, Fu J, Catalytic Decarboxylation and Aromatization of Oleic Acid over Ni / AC without an Added Hydrogen Donor. Industrial & Engineering Chemistry Research, 2018, 57, 8443-8448) studied the effect of Ni loading on the performance of Ni / AC catalyst in oleic acid catalytic deoxygenation reaction under non-hydrogen conditions. The results show that the adsorption capacity of 30wt% Ni / AC catalyst for CH3COOH is higher than that of other Ni / AC catalysts, and the Ni particles are highly dispersed and small, achieving a heptadecane yield of 40.7% and showing good stability.
[0005] Intermetallic compounds are compounds composed of two or more metals and metalloids with integer stoichiometric ratios. Due to the ordered structure of their crystals and the coexistence of metallic bonds and covalent bonds, they have a series of unique excellent properties, such as low density, high specific stiffness, high melting point, good high temperature strength and excellent antioxidant properties. Therefore, it is very necessary to develop a Ni-based bimetallic compound with good non-hydrogen catalytic deoxidation performance of fatty acids. Summary of the invention
[0006] The purpose of the present invention is to construct a cheap and efficient non-hydrogenation deoxygenation catalyst for fatty acids, which effectively improves the catalytic activity through the synergistic effect of bimetallic, geometric modification, electronic modification and the like.
[0007] The technical solution provided by the present invention is:
[0008] A supported FeNi bimetallic catalyst, wherein the active components of the catalyst are an alloy compound with high dispersion composed of Fe and Ni doped with each other, wherein the iron content is 5-15%, and the nickel content is 5-21%. The catalyst carrier is selected from one or more of activated carbon, Al2O3, ZrO2, TiO2, Co3O4, and CeO2, and the particle size of the catalyst is 50 to 200 nm.
[0009] In some embodiments, the catalyst carrier is activated carbon, the particle size of the catalyst is 80nm to 180nm, in some embodiments, the particle size of the catalyst is 90nm, 100nm, 120nm, 130nm, 140nm, 150nm, 170nm, 180nm or 190nm. In some embodiments, the FeNi intermetallic compound is a FeNi3 phase.
[0010] A method for preparing a supported FeNi bimetallic catalyst comprises: dissolving a metal precursor in deionized water, mixing with a catalyst carrier, ultrasonicating, stirring at room temperature for 5 to 24 hours, drying, and calcining at 500 to 900° C. for 2 to 10 hours in an inert atmosphere to obtain a supported FeNi catalyst.
[0011] In some embodiments, the catalyst carrier is selected from one or more of activated carbon, Al2O3, ZrO2, TiO2, Co3O4, and CeO2. In some embodiments, the catalyst carrier is activated carbon.
[0012] In some embodiments, the metal precursor may include an iron salt or a nickel salt, and the iron salt or the nickel salt may include a combination of two or more of nickel nitrate hexahydrate, nickel chloride, nickel acetylacetonate, ferric nitrate nonahydrate, and ferric chloride.
[0013] In some embodiments, the metal precursors are ferric nitrate and nickel nitrate, and the molar ratio thereof is (3-0.33):1, preferably 0.33:1.
[0014] In some embodiments, the stirring time is 2 to 24 hours, preferably 4 hours, and the stirring is performed at a speed of 500 rpm for 5 to 24 hours.
[0015] In some embodiments, the inert atmosphere is an inert gas containing more than 90% argon, such as 5% H2 / Ar atmosphere or 100% argon atmosphere, and the calcination temperature is 500-900°C. In some embodiments, the calcination temperature is 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C.
[0016] In some embodiments, the inert atmosphere is a 5% H2 / Ar atmosphere, and the calcination temperature is 500-700°C, preferably 500°C.
[0017] In some embodiments, when metallic iron and metallic nickel are loaded onto a catalyst carrier, the FeNi alloy particle size is 50 to 150 nm. In the above technical solution, the content of iron is 5 to 15%, the content of nickel is 5 to 21% prepared by adsorption reduction method, and the iron metal and nickel metal are uniformly dispersed on the carrier.
[0018] The supported FeNi bimetallic catalyst prepared above is used for non-hydrogenation catalytic deoxygenation of fatty acids, comprising the following steps: adding the supported FeNi catalyst to fatty acids, heating to 300-360° C. and reacting for 10-100 minutes.
[0019] The fatty acid deoxygenation takes place in a 2 mL microreactor (Swaglok) with a maximum pressure resistance of 68 MPa and a maximum temperature resistance of 800°C.
[0020] The mass ratio of the fatty acid to the supported FeNi catalyst is (20-1):1, preferably 3.33:1.
[0021] The reaction temperature of the fatty acid and the supported FeNi catalyst is 300-360°C, preferably 360°C.
[0022] The reaction time of the fatty acid and the supported FeNi catalyst is 30 to 90 minutes, preferably 60 minutes.
[0023] The FeNi catalyst of the present invention is suitable for catalytic dehydrogenation of various fatty acids. For example, in some embodiments, the fatty acids may include stearic acid, lauric acid or myristic acid. In the embodiments of the present invention, stearic acid is used to verify the catalytic activity of the catalyst.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] (1) The present invention adopts an adsorption reduction method to prepare a supported FeNi bimetallic catalyst, which has a simple preparation process, is convenient for mass production, has a low transition metal loading, and has a low production cost.
[0026] (2) The supported FeNi catalyst synthesized in the present invention has good deoxidation activity and stability due to the synergistic effect of the bimetallic and electronic modification. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 TEM image of FeNi3 / AC-900 in Example 14.
[0028] Figure 2 XRD patterns of FeNi3 / AC, FeNi3 / AC-700 and FeNi3 / AC-900 in Examples 12 to 14. DETAILED DESCRIPTION
[0029] The metal loading of the catalyst in the examples of the present invention was detected by inductively coupled plasma mass spectrometry (ICP-OES, Agilent, 5100SVDV).
[0030] The particle size of the catalyst was analyzed by scanning electron microscopy (SEM, ZEISS Sigma). The sample was dried overnight in an oven, the conductive glue was glued to the sample stage, and then a small amount of sample was applied to the conductive glue and purged with an ear bulb. The sample stage was transferred to a platinum sprayer and platinum was sprayed at 30 mA for 30 seconds. The sample stage was then transferred to the sample chamber and evacuated for subsequent analysis. The instrument operating voltage was 15 kV, and observation was performed from high to low magnification.
[0031] A transmission electron microscope (TEM, FEI Talos F200x) was used to further analyze the microscopic morphology of the sample, and an energy dispersive spectrometer (EDS) was used to analyze the spatial distribution of elements in the sample. The sample was pretreated before the test. A small amount of sample was placed in a centrifuge tube, anhydrous ethanol was added, and then ultrasonically treated in an ultrasonic cleaner for 20 minutes. A small amount of suspension was then applied to the copper mesh, and then dried for subsequent analysis. The copper mesh was fixed on the sample rod, and the test working voltage was adjusted to 300kV after vacuuming for testing.
[0032] The quantitative analysis of the samples in the embodiment uses a gas chromatograph (GC-FID, Agilent7890A) with a hydrogen flame detector, and the chromatographic column model is E798717KB-FFAP gas chromatographic column (column temperature 260°C). The injection conditions are injection temperature 260°C, injection volume 1μL; carrier gas is high-purity N2, carrier gas flow rate 11.38mL / min, split ratio 10:1. 25mL / min of N2 is used for tail gas purge in FID, the standard air flow rate is 400mL / min, and the flow rate of high-purity H2 is 30mL / min. The FID detection temperature is 250°C, and the temperature rise program of the column box is: starting temperature 150°C, hold 8min, then heat to 240°C at a heating rate of 20°C / min, and hold 18min.
[0033] The characteristics of the catalyst in the embodiment of the present invention are detected by powder X-ray diffraction, the test range is 10° to 90°, the radiation source is CuKα (λ=0.15418nm), the test tube voltage is 35KV, the current is 15mA and the corresponding scanning rate is 10° / min.
[0034] The present invention is described in detail below by way of examples, but the present invention is not limited to the examples.
[0035] Example 1
[0036] 0.2020g of Fe(NO3)3·9H2O and 0.1454g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2291g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi / AC.
[0037] 60 mg of stearic acid and 18 mg of catalyst FeNi / AC were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 93.5%, the deoxygenation rate was 90.5%, the selectivity of heptadecane was 74.7%, and the selectivity of heptadecaene was 22.0%.
[0038] Example 2
[0039] 0.2020g of Fe(NO3)3·9H2O and 0.1454g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2291g of Al2O3 was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi / Al2O3.
[0040] 60 mg of stearic acid and 18 mg of catalyst FeNi / Al2O3 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 53.1%, the deoxygenation rate was 45.2%, the selectivity of heptadecane was 65.7%, and the selectivity of heptadecaene was 16.6%.
[0041] Example 3
[0042] 0.2020g of Fe(NO3)3·9H2O and 0.1454g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2291g of ZrO2 was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an oven at 80℃ to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi / ZrO2.
[0043] 60 mg of stearic acid and 18 mg of catalyst FeNi / ZrO2 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 49.5%, the deoxygenation rate was 44.5%, the selectivity of heptadecane was 67.6%, and the selectivity of heptadecaene was 16.5%.
[0044] Example 4
[0045] 0.2020g of Fe(NO3)3·9H2O and 0.1454g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2291g of TiO2 was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an oven at 80℃ to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi / TiO2.
[0046] 60 mg of stearic acid and 18 mg of catalyst FeNi / TiO2 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 79.6%, the deoxygenation rate was 72.7%, the selectivity of heptadecane was 68.4%, and the selectivity of heptadecaene was 13.7%.
[0047] Example 5
[0048] 0.2020g of Fe(NO3)3·9H2O and 0.1454g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2291g of Co3O4 was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi / Co3O4.
[0049] 60 mg of stearic acid and 18 mg of catalyst FeNi / Co3O4 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 70.9%, the deoxygenation rate was 62.7%, the selectivity of heptadecane was 64.2%, and the selectivity of heptadecaene was 18.1%.
[0050] Example 6
[0051] 0.2020g of Fe(NO3)3·9H2O and 0.1454g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2291g of CeO2 was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an oven at 80℃ to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi / CeO2.
[0052] 60 mg of stearic acid and 18 mg of catalyst FeNi / CeO2 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 9.4%, the deoxygenation rate was 8.6%, the selectivity of heptadecane was 71.0%, and the selectivity of heptadecaene was 7.8%.
[0053] Example 7
[0054] 0.4040g of Fe(NO3)3·9H2O was dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2234g of activated carbon was slowly added to the solution, and continued to stir at 500rpm for 4h at room temperature, the solution was placed in an oven at 80℃ for drying, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named Fe / AC.
[0055] 60 mg of stearic acid and 18 mg of catalyst Fe / AC were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 83.4%, the deoxygenation rate was 74.7%, the selectivity of heptadecane was 70.1%, and the selectivity of heptadecaene was 9.7%.
[0056] Example 8
[0057] 0.2910g Ni(NO3)2·6H2O was dissolved in 10mL deionized water, stirred at 500rpm for 1h at room temperature, 0.2291g activated carbon was slowly added to the solution, and continued to stir at 500rpm for 4h at room temperature, the solution was placed in an oven at 80℃ to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named Ni / AC.
[0058] 60 mg of stearic acid and 18 mg of catalyst Ni / AC were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 87.6%, the deoxygenation rate was 87.6%, the selectivity of heptadecane was 72.7%, and the selectivity of heptadecaene was 22.0%.
[0059] Example 9
[0060] 0.3030g of Fe(NO3)3·9H2O and 0.0728g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2262g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named Fe3Ni / AC.
[0061] 60 mg of stearic acid and 18 mg of catalyst Fe3Ni / AC were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 85.8%, the deoxygenation rate was 79.8%, the selectivity of heptadecane was 68.4%, and the selectivity of heptadecaene was 11.9%.
[0062] Example 10
[0063] 0.2693g of Fe(NO3)3·9H2O and 0.0970g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2272g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named Fe2Ni / AC.
[0064] 60 mg of stearic acid and 18 mg of catalyst Fe2Ni / AC were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 86.2%, the deoxygenation rate was 81.7%, the selectivity of heptadecane was 75.5%, and the selectivity of heptadecaene was 14.5%.
[0065] Embodiment 11
[0066] 0.1347g of Fe(NO3)3·9H2O and 0.1940g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an oven at 80℃ to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi2 / AC.
[0067] 60 mg of stearic acid and 18 mg of catalyst FeNi2 / AC were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 93.2%, the deoxygenation rate was 89.7%, the selectivity of heptadecane was 71.8%, and the selectivity of heptadecaene was 21%.
[0068] Example 12
[0069] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an oven at 80℃ to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi3 / AC.
[0070] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 94.2%, the deoxygenation rate was 89.9%, the selectivity of heptadecane was 70.4%, and the selectivity of heptadecaene was 20.1%.
[0071] Example 13
[0072] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 700℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 700℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi3 / AC-700.
[0073] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC-700 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 97.5%, the deoxygenation rate was 93.7%, the selectivity of heptadecane was 65.2%, and the selectivity of heptadecaene was 28.3%.
[0074] Embodiment 14
[0075] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 900℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 900℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi3 / AC-900.
[0076] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC-900 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 98.9%, the deoxygenation rate was 95.6%, the selectivity of heptadecane was 70.0%, and the selectivity of heptadecaene was 27.0%.
[0077] Embodiment 15
[0078] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 500℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 500℃ for 5h, and naturally cooled to room temperature to obtain a supported FeNi catalyst. The catalyst was named FeNi3 / AC-500-A.
[0079] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC-500A were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1.5 h. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 89.7%, the deoxygenation rate was 84.2%, the selectivity of heptadecane was 70.1%, and the selectivity of heptadecaene was 19.1%.
[0080] Example 16
[0081] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 900℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 900℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi3 / AC-900.
[0082] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC-900 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 340°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 93.6%, the deoxygenation rate was 90.5%, the selectivity of heptadecane was 69.6%, and the selectivity of heptadecaene was 28.1%.
[0083] Embodiment 17
[0084] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 900℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 900℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi3 / AC-900.
[0085] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC-900 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 320°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 88.3%, the deoxygenation rate was 84.4%, the selectivity of heptadecane was 67.3%, and the selectivity of heptadecaene was 28.3%.
[0086] Embodiment 18
[0087] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 900℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 900℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi3 / AC-900.
[0088] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC-900 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 300°C for 1 hour. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 64.3%, the deoxygenation rate was 63.2%, the selectivity of heptadecane was 73.1%, and the selectivity of heptadecaene was 25.2%.
[0089] Embodiment 19
[0090] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 900℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 900℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi3 / AC-900.
[0091] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC-900 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 0.5 h. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 86.3%, the deoxygenation rate was 82.5%, the selectivity of heptadecane was 68.7%, and the selectivity of heptadecaene was 26.1%.
[0092] Embodiment 20
[0093] 0.1010g of Fe(NO3)3·9H2O and 0.2228g of Ni(NO3)2·6H2O were dissolved in 10mL of deionized water, stirred at 500rpm for 1h at room temperature, 0.2310g of activated carbon was slowly added to the above solution, and continued to stir at 500rpm for 4h at room temperature, the above solution was placed in an 80℃ oven to dry, the dried sample was transferred to a tube furnace, heated to 900℃ at a rate of 2℃ / min in an Ar atmosphere, calcined at 900℃ for 5h, cooled naturally to room temperature, then heated to 500℃ at a rate of 2℃ / min in a 5% H2 / Ar atmosphere, calcined at 500℃ for 2h, and cooled naturally to room temperature to obtain a supported FeNi catalyst. The catalyst is named FeNi3 / AC-900.
[0094] 60 mg of stearic acid and 18 mg of catalyst FeNi3 / AC-900 were added to the microreactor, which was sealed and placed in a muffle furnace for heating to 360°C for 1.5 h. After the reaction, the product was collected for analysis and used for subsequent GC-FID detection and analysis. The product conversion rate was 99.2%, the deoxygenation rate was 95.8%, the selectivity of heptadecane was 70.2%, and the selectivity of heptadecaene was 26.6%.
Claims
1. Application of a supported FeNi bimetallic catalyst in non-hydrogenation catalytic deoxygenation of stearic acid, wherein the preparation method of the supported FeNi bimetallic catalyst comprises: The metal precursor is dissolved in deionized water and mixed with the catalyst carrier, ultrasonicated, stirred at room temperature for 5 to 24 hours, and then dried to obtain a solid powder, the solid powder is placed in an argon atmosphere, and calcined at 500 to 900 ° C for 2 to 10 hours; then, reduced at 500 to 700 ° C for 2 hours in a 5% H2 / Ar atmosphere; the metal precursor includes an iron salt or a nickel salt; The catalyst carrier of the supported FeNi bimetallic catalyst is activated carbon, wherein the Fe content is 5-15%, the Ni content is 5-21%, and the molar ratio of Fe to Ni is 1:2 or 1:3; the particle size of the FeNi bimetallic catalyst is 50 to 200 nm; The application of the supported FeNi bimetallic catalyst in the non-hydrogen catalytic deoxygenation of stearic acid comprises the following steps: adding the supported FeNi bimetallic catalyst to stearic acid for deoxygenation, wherein the stearic acid deoxygenation occurs at a temperature of 340 to 360° C. and the reaction time is 1 to 1.5 hours.
2. The use according to claim 1, characterized in that: The iron salt is iron nitrate or iron chloride, and the nickel salt is nickel nitrate or nickel acetylacetonate.
3. The use according to claim 1, characterized in that: The metal precursors are ferric nitrate and nickel nitrate, and the molar ratio thereof is 0.33:
1.
4. The use according to claim 1, characterized in that: The stearic acid deoxygenation occurs in a 2 mL microreactor with a maximum pressure resistance of 68 MPa and a maximum temperature resistance of 800° C. The mass ratio of the stearic acid to the supported FeNi bimetallic catalyst is (20-1):
1.
5. The use according to claim 1, characterized in that: The stearic acid deoxygenation occurs in a 2 mL microreactor with a maximum pressure resistance of 68 MPa and a maximum temperature resistance of 800° C. The mass ratio of the stearic acid to the supported FeNi bimetallic catalyst is 3.33:1.
Citation Information
Patent Citations
production of LINEAR HYDROCARBONS BY DECARBOXYLATION OF CARBOXYLIC FATTY ACIDS IN THE PRESENCE OF A SUPPORTED BIMETALLIC CATALYST
FR3066193A1